Search for new physics in high-mass electron-positron events in pp[over] collisions at square root s = 1.96 TeV. - Aaltonen, T; Abulencia, A; Adelman, J; Affolder, T; Akimoto, T; Albrow, MG; Amerio, S; Amidei, D; Anastassov, A; Anikeev, K; Annovi, A; Antos, J; et al. (2007)
We report the results of a search for a narrow resonance in electron-positron events in the invariant mass range of 150-950 GeV/c(2) using 1.3 fb(-1) of pp[over] collision data at square root s = 1.96 TeV collected by the CDF II detector at Fermilab. No significant evidence of such a resonance is observed and we interpret the results to exclude the standard-model-like Z' with a mass below 923 GeV/c(2) and the Randall-Sundrum graviton with a mass below 807 GeV/c(2) for k/M[over](pl) = 0.1, both at the 95% confidence level. Combining with diphoton data excludes the Randall-Sundrum graviton for masses below 889 GeV/c(2) for k/M[over](pl) = 0.1.